Exchanges of sediment between the flood plain and channel of the Amazon River in Brazil - Dunne, Thomas; Mertes, Leal A.K.; Meade, Robert H.; Richey, Jeffrey E.; Forsberg, Bruce Rider (Bulletin of the Geological Society of America, 1998)
Sediment transport through the Brazilian sector of the Amazon River valley, a distance of 2010 km, involves exchanges between the channel and the flood plain that in each direction exceed the annual flux of sediment out of the river at Óbidos (∼1200 Mt yr-1). The exchanges occur through bank erosion, bar deposition, settling from diffuse overbank flow, and sedimentation in flood-plain channels. We estimated the magnitude of these exchanges for each of 10 reaches of the valley, and combined them with calculations of sediment transport into and out of the reaches based on sediment sampling and flow records to define a sediment budget for each reach. Residuals in the sediment budget of a reach include errors of estimation and erosion or deposition within the channel. The annual supply of sediment entering the channel from bank erosion was estimated to average 1570 Mt yr-1 (1.3 × the Óbidos flux) and the amount transferred from channel transport to the bars (380 Mt yr-1) and the flood plain (460 Mt yr-1 in channelized flow; 1230 Mt yr-1 in diffuse overbank flow) totaled 2070 Mt yr-1 (1.7 × the Óbidos flux). Thus, deposition on the bars and flood plain exceeded bank erosion by 500 Mt yr-1 over a 10-16 yr period. Sampling and calculation of sediment loads in the channel indicate a net accumulation in the valley floor of approximately 200 Mt yr-1 over 16 yr, crudely validating the process-based calculations of the sediment budget, which in turn illuminate the physical controls on each exchange process. Another 300-400 Mt yr-1 are deposited in a delta plain downstream of Óbidos. The components of the sediment budget reflect hydrologie characteristics of the valley floor and geomorphic characteristics of the channel and flood plain, which in turn are influenced by tectonic features of the Amazon structural trough.
Keywords: Banks (bodies Of Water); Budget Control; Erosion; Floods; Floors; Sediment Transport; Sedimentation; Channelized Flow; Exchange Process; Overbank Flow; Physical Control; Sediment Budgets; Sediment Loads; Sediment Sampling; Tectonic Features; Rivers; Bank Erosion; Floodplain; Overbank Flow; River Channel; Sediment Budget; Sediment Transport; Sedimentation Rate; Trough; Amazon River; Floodplain; Fluvial Sediment; River Channel; Sediment Transport